Relationship Between Lower Limb Tightness and Practice Time Among Adolescent Baseball Players With Symptomatic Osgood-Schlatter Disease. Issue 5 (27th May 2019) - Omodaka, Takuya; Ohsawa, Takashi; Tajika, Tsuyoshi; Shiozawa, Hiroyuki; Hashimoto, Syogo; Ohmae, Hiroaki; Shitara, Hitoshi; Ichinose, Tsuyoshi; Sasaki, Tsuyoshi; Hamano, Noritaka; Takagishi, Kenji; Chikuda, Hirotaka
Background: Osgood-Schlatter disease (OSD) is characterized by traction apophysitis of the tibial tuberosity. Few studies on symptomatic and asymptomatic OSD have correlated findings with clinical examination. Purpose: To investigate the relationship between lower limb tightness and practice time among adolescent baseball players with symptomatic OSD. Study Design: Cross-sectional study; Level of evidence, 3. Methods: The study participants were 402 male baseball players (N = 804 knees) with a mean ± SD age of 10.9 ± 1.5 years (range, 7-14 years). Participant age, height, body weight, body mass index, practice time per week, range of motion of the hip and ankle joints, heel-buttock distance (HBD), and straight-legged raise angle were evaluated. Tibial tuberosity development, as assessed with ultrasonography, was classified into 4 stages: cartilaginous, apophyseal, epiphyseal, and bony. Knees that were classified as apophyseal or epiphyseal were investigated. Participants were divided into 3 groups: non-OSD, asymptomatic OSD, and symptomatic OSD. Results: Of 400 knees in the apophyseal and epiphyseal stages, 23 knees had asymptomatic OSD, and 11 had symptomatic OSD. Players with symptomatic OSD practiced for significantly longer than the non-OSD group ( P = .001) and asymptomatic OSD group ( P = .001). Players with symptomatic OSD also had a larger HBD ( P = .006) and smaller range of motion regarding internal rotation of hip ( P = .023) and dorsiflexion of the ankle ( P = .013) than the non-OSD group. Conclusion: Players with symptomatic OSD had longer practice times than the non-OSD and asymptomatic OSD players. Symptomatic OSD was also associated with tightness of the lower limbs as assessed by the HBD and range of motion in the hip and ankle joints.